Isolation and characterization of atypical Actinobacillus pleuropneumoniae serovar 15 lacking the apxIICA genes in Japan - TESHIMA, Kaho (J Vet Med Sci, 2019)
Six atypical Actinobacillus pleuropneumoniae serovar 15 strains were isolated from pneumonic lesions of naturally infected dead pigs from the same farm in Japan. Genetic analyses of apx genes revealed that the atypical isolates contained the toxin-associated genes apxIBD, apxIIICA, apxIIIBD, and apxIVA, but not apxIICA. Coinciding with the result of the atypical gene profile, analyses of toxin protein production revealed that these atypical isolates expressed only ApxIII but not ApxII. A mouse pathogenicity test showed that the atypical isolate tested seemed to be less virulent than the typical isolates. This is the first report describing the emergence of atypical A. pleuropneumoniae serovar 15, which does not produce ApxII due to the absence of apxIICA genes, in Japan.